Shucked apart - Ross, Barbara, 1953- (Ross, Barbara, 1953- Maine clambake mystery., 2021)
When oyster farmer Andia Greatorex is murdered after being robbed of a bucket of oyster seed worth $35,000, Julia Snowden decides to help the Maine State police major crimes unit investigate before someone else ends up in a watery grave.